Optimizing Nutritional Status and Improving Quality of Life: Comprehensive Study of Chronic Kidney Failure Patients Undergoing Hemodialysis at Luwuk Regional Hospital - Wijianto, Wijianto; Tamrin, Ike Nurjanah; Hasan, Sri Murniawati; Asomah, Nur Eli (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Chronic kidney disease (CKD) is a progressive disorder that affects kidney function, often requiring interventions like hemodialysis to maintain patient stability. In addition to medical care, it is crucial to consider patients' nutritional status and quality of life. This cross-sectional study aimed to determine the nutritional status and quality of life of CKD patients undergoing hemodialysis at Luwuk Regional Hospital. The study included 77 subjects, and nutritional status was assessed using the Dialysis Malnutrition Score (DMS), while quality of life was measured using the Kidney Disease Quality of Life Short Form (KDQoL-SF). The results showed that 72.7% of subjects had normal/good nutritional status, and 27.3% had mild-moderate malnutrition. Furthermore, 51.9% of subjects reported poor quality of life, while 48.1% had good quality of life. Among subjects with good nutritional status, 39.7% had good quality of life, and 60.7% had poor quality of life. Statistical analysis revealed no significant relationship between nutritional status based on DMS and quality of life in hemodialysis patients (p>0.05). Quality of life is a complex phenomenon influenced by various factors, and good nutritional status alone may not be sufficient to improve quality of life if other factors, such as psychological stress or pain, are not properly managed. The findings emphasize the importance of a holistic, multidimensional, and personalized clinical approach to enhance the quality of life in hemodialysis patients. Interventions should not only focus on improving nutritional status but also consider patients' overall psychological, social, and physical well-being.